The Impact of Mining Activities on The Living Conditions of Bombana District Communities - Ido, Irfan; Alwi, La Ode; Isma, Wa (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2017)
The purpose of this research is to explain the impact of mining activities on the living conditions of Bombana District people. The research was conducted in North Rarowatu Sub-District, Wumbubangka Village and Lantowua Village, with determination of 133 samples from two villag es. The data were analyzed in descriptions method using cross tabulation and frequency table with eleven variables that is: the rate of air changes, the level of noise pollution, the level of disruption to water availability, the number of affected households, the frequency of treatment, the level of education, the conditions of residence, the status of residence, the conflict between local communities, the level of depth of conflict, employment opportunities. The results of the research indicate the impact of mining activities on the living conditions of Bombana district communities, especially in the two villages. On the ecological aspect of air conditions, mining activity causes the air condition to getmoreworst.In addition, mine activity raises noise that disrupts community activities, and a small proportion of groundwater availability is not available. On the social aspect there are still a number of community members who suffer from respiratory problems such as shortness of breath, cough and cold, from the frequency of treatment only a fewof them do a treatment. The low level of education in these two villagesis the cause of employment opportunities decrease. From the residence's condition and the residence statusarestill relatively decent and medium. In addition, the changes in environmental conditions lead to conflictbetween the local community and the company